2009
DOI: 10.1111/j.1365-2869.2009.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Central apnoeas have significant effects on blood pressure and heart rate in children

Abstract: Summary Brief central apnoeas (CAs) during sleep are common in children and are not usually considered clinically significant unless associated with oxygen desaturation. CAs can occur spontaneously or following a movement or sigh. The aim of this study was to investigate acute cardiovascular changes associated with CAs in children. Beat‐by‐beat mean arterial pressure (MAP) and heart rate (HR) were analysed across CAs, and spontaneous and movement‐induced events were compared using two‐way analysis of variance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Also similar to the previous study, the surge in BP at the termination of an event was much smaller compared with HR. Previous studies have identified that both isolated obstructive and central events in children have similar cardiovascular sequelae to isolated obstructive events in adults (10,14). The episodes of repetitive respiratory events included in this study, included substantial numbers of central events.…”
Section: Repetitive Respiratory Events In Childrenmentioning
confidence: 95%
See 4 more Smart Citations
“…Also similar to the previous study, the surge in BP at the termination of an event was much smaller compared with HR. Previous studies have identified that both isolated obstructive and central events in children have similar cardiovascular sequelae to isolated obstructive events in adults (10,14). The episodes of repetitive respiratory events included in this study, included substantial numbers of central events.…”
Section: Repetitive Respiratory Events In Childrenmentioning
confidence: 95%
“…Central apneas have been described in healthy children during sleep and are known to decrease with age (12,13). A similar cardiovascular response is also associated with central apneas in children with SDB (14). In addition, respiratory events may be associated with hypoxia and arousal, both of which have cardiovascular sequelae, increasing BP, HR, and sympathetic activity (15)(16)(17)(18).…”
mentioning
confidence: 91%
See 3 more Smart Citations